1994
DOI: 10.1165/ajrcmb.11.6.7946399
|View full text |Cite
|
Sign up to set email alerts
|

Alveolar epithelial cells express and secrete parathyroid hormone-related protein.

Abstract: Parathyroid hormone-related protein (PTHrP) was discovered as a hypercalcemia-inducing product of malignant cells and has since been demonstrated to be a product of many tissues. Although it is robustly expressed in fetal lung, PTHrP expression has not been assigned to alveolar epithelial cells in adult lung. We have shown that PTHrP is expressed in the adult rat lung and by cultured rat alveolar type II epithelial cells with sensitive and specific immunoassays and immunohistochemical techniques. Immunoassay o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2000
2000
2009
2009

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 24 publications
1
23
0
Order By: Relevance
“…von Kossa's stain, ×200 lial cells. [3,9,14,18], although the physiological functions in normal lung tissues have yet to be determined. In the present study, it was demonstrated by the immunohistochemistry, the RT-PCR method, and IRMA using culture supernatants that IP tumor cells produce PTHrP.…”
Section: Discussionmentioning
confidence: 99%
“…von Kossa's stain, ×200 lial cells. [3,9,14,18], although the physiological functions in normal lung tissues have yet to be determined. In the present study, it was demonstrated by the immunohistochemistry, the RT-PCR method, and IRMA using culture supernatants that IP tumor cells produce PTHrP.…”
Section: Discussionmentioning
confidence: 99%
“…Thus amniotic fluid PTHrP could stimulate epithelial growth and differentiation (Kaiser et al 1994) and may assist in the maturation of these tissues and organs. During fetal lung development, PTHrP is predominantly expressed in bronchial epithelia and alveolar type II cells, whereas its receptor is found in the subepithelial mesenchyme (Hastings et al 1994, Rubin et al 1994. PTHrP-deficient mice were found to have lung hypoplasia, arrested canalicular development and impaired epithelial cytodifferentiation (Rubin et al 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Regulation of PTHrP release by PKC has been reported in the NCI-H727 nonsmall lung cancer cell line, alveolar epithelial cells, and human osteosarcoma cell line [121][122][123]. In some cell systems, PKC participates in activation of MEK/ERK cascade [124,125].…”
Section: Regulation By Pkc/mek Pathwaymentioning
confidence: 99%